Preparation and properties of nanocomposite coatings on sintered NdFeB magnets. (18th July 2018) - Shen, Lida; Fan, Mingzhi; Zhao, Kailin; Qiu, Mingbo; Tian, Zongjun
Abstract: To enhance corrosion resistance of sintered NdFeB magnets, Ni–Al2 O3 nanocomposite coatings were prepared on the magnets by pulsed current-jet electrodeposition. The effects of average current density and nanoparticles on the properties of coatings were evaluated. The surface morphology, microstructure, adhesion strength, and corrosion resistance of coatings were characterized by scanning electron microscopy, x-ray diffraction, scratch tester, and electrochemical workstation, respectively. The results showed that proper increase of current density was beneficial to the performance of coatings, and that protective properties of coatings decreased when the current density exceeded 120 A dm −2 . Properties of coatings were enhanced by the addition of nanoparticles. Nanocomposite coatings showed better adhesion strength and corrosion resistance than pure nickel coatings.